FORMULASI KEPEMIMPINAN VISIONER DALAM MENINGKATKAN BUDAYA MUTU PENDIDIKAN ISLAM MADRASAH - Siswadi, Siswadi (Jurnal Manajemen Pendidikan, 2025)
This study aims to analyse the application of visionary leadership in enhancing the culture of quality in Islamic education within madrasahs. Visionary leadership is regarded as a future-oriented leadership style, characterised by the ability to formulate a clear and inspiring vision, and to mobilise all elements of the madrasah towards a shared goal. The research method employed was a literature review, examining various relevant literature, research findings, and theories concerning visionary leadership, a culture of quality, and the context of Islamic education. The findings indicate that the visionary leadership of madrasah heads plays a strategic role in strengthening educational quality through systematic planning, the development of a vision and mission grounded in Islamic values, the strengthening of organisational culture, and the effective management of resources. Furthermore, visionary leadership also fosters the professional development of teachers, student achievement, and the integration of spiritual and moral values into every aspect of educational governance. The implications of this research underscore the importance of strengthening the strategic leadership competencies of madrasah heads through continuous training, the development of collaborative networks, and the implementation of internal quality management systems. Thus, the formulation of visionary leadership can serve as a transformative paradigm in building a culture of excellence in Islamic madrasah education that is of high quality, integrity, and adaptable to global challenges.